Provisioning of Applications with Network Requirements on Cloud-Edge Continuum - Albuquerque, Paulo Roberto; Koslovski, Guilerme Piêgas (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS); 2024: Anais da XXIV Escola Regional de Alto Desempenho da Região SulDO - 10.5753/eradrs.2024.238747, 2024)
New challenges regarding the users mobility and network latency are observed in the provisioning of distributed applications atop Cloud Continuum scenarios. This requires a analysis from the perspectives of users and service providers. This article proposes a way to create provisioning policies based on user mobility and mass demands, while also analyzing the individual Services that compose some Application, analyzing their needs and restrictions.